Effect of petrophysical matrix properties on bypassed oil recovery from a matrix-fracture system during CO2 near-miscible injection: Experimental investigation. (October 2016) - Bejestani, Danial Zeinabady; Rostami, Behzad; Khosravi, Maryam; Kazemi, Keyvan
Highlights: The efficiency of near-miscible injection in bypassed oil recovery is investigated. The relative importance of active mechanisms in bypassed oil recovery is demonstrated. The effect of petrophysical properties on near-critical-point-wetting is studied. Abstract: The effects of petrophysical matrix properties such as porosity and permeability on bypassed oil recovery were investigated during CO2 injection in fractures at different miscibility regimes (first-contact miscibility, near-miscibility, and immiscibility). A special experimental setup was designed for this purpose and a series of CO2 injection experiments were performed using two different types of porous media, sandstones and carbonates. To confirm the analysis, some tests were repeated in the presence of irreducible water saturation. In addition, dimensional analysis was used to capture the dominant forces and mechanisms. The results demonstrated that the highest oil recovery was achieved within near-miscible regime for the both rock types. Furthermore, in all miscibility regimes, the oil recovery factor decreased with the increase of the rock complexity and frequency of dead-end pores, whereas it declined as the permeability decreased. However, differences in recovery factors of near-critical and super-critical tests grew. Considering the analytical calculations and the results of experiments including initial water saturation, it can be concluded that near-critical point wetting and the number of dead-end pores have significant effects on variations of the oil recovery factor. With near-critical point wetting, maximum recovery was achieved at near-critical state, and the presence of dead-end pores caused the role of this mechanism to be more noticeable. As a result, differences in the recovery factor of near-critical and super-critical tests grew.